Patient education and follow-up units in Iran: A quality improvement project - Elham Almassi Ghaleh; Susan Jamshidi Farsani; Parastoo Ariamloo; Nasrin Mehrnoosh; Maryam Rassouli; Abbas Ebadi (Nursing Practice Today)
Background & Aim: The rising prevalence of chronic and non-communicable diseases, presents significant challenges to health systems. This study aims to empower patients and their families by establishing patient education and follow-up units, thereby improving readmission rates, reducing unplanned referrals to emergency departments, and enhancing patient satisfaction, which are key nursing-sensitive indicators. Methods & Materials: This perspective article presents a quality improvement project utilizing the Plan-Do-Study-Act cycle model. Initially, the problem of non-compliance among discharged patients and the resulting adverse consequences were identified. Consequently, a program for patient and family education and follow-up post-discharge was proposed. In the second step, patient education and follow-up units were implemented across three universities of medical sciences, and the results were analyzed in the third step. Upon confirming the achievement of the expected outcomes, the fourth step involved the national dissemination of implementation guidelines. Results: The established units in hospitals demonstrated significant improvements in NSIs. The percentage of readmission among follow-up patients decreased from 14.3% in the first half of 2023 to 6.6% in the first half of 2024. The indicator of unplanned referrals dropped from 8.93% to 6.1% over the same period. Additionally, patient satisfaction increased from 91% to 93%. Conclusion: The experience of establishing patient education and follow-up units highlights that this strategy during the transition to home is an effective, affordable, and sustainable solution that can improve NSIs. This approach, facilitated by nurses, can play a crucial role in managing non-communicable and chronic diseases.